Susceptibility to hormone-mediated cancer is reflected by different tick rates of the epithelial and general epigenetic clock - Barrett, James E; Herzog, Chiara; Kim, Yoo-Na; Bartlett, Thomas E; Jones, Allison; Evans, Iona; Cibula, David; Zikan, Michal; Bjørge, Line; Harbeck, Nadia; Colombo, Nicoletta; Howell, Sacha J; et al. (Genome biology, 2022)
BACKGROUND: A variety of epigenetic clocks utilizing DNA methylation changes have been developed; these clocks are either tissue-independent or designed to predict chronological age based on blood or saliva samples. Whether discordant tick rates between tissue-specific and general epigenetic clocks play a role in health and disease has not yet been explored. RESULTS: Here we analyze 1941 cervical cytology samples, which contain a mixture of hormone-sensitive cervical epithelial cells and immune cells, and develop the WID general clock (Women's IDentification of risk), an epigenetic clock that is shared by epithelial and immune cells and optimized for cervical samples. We then develop the WID epithelial clock and WID immune clock, which define epithelial- and immune-specific clocks, respectively. We find that the WID-relative-epithelial-age (WID-REA), defined as the difference between the epithelial and general clocks, is significantly reduced in cervical samples from pre-menopausal women with breast cancer (OR 2.7, 95% CI 1.28-5.72). We find the same effect in normal breast tissue samples from pre-menopausal women at high risk of breast cancer and show that potential risk reducing anti-progesterone drugs can reverse this. In post-menopausal women, this directionality is reversed. Hormone replacement therapy consistently leads to a significantly lower WID-REA in cancer-free women, but not in post-menopausal women with breast or ovarian cancer. CONCLUSIONS: Our findings imply that there are multiple epigenetic clocks, many of which are tissue-specific, and that the differential tick rate between these clocks may be an informative surrogate measure of disease risk.
Keywords: Aging; epigeneze genetická; Animals; DNA Methylation; Ticks; lidé; ženské pohlaví; metylace DNA; Breast Neoplasms; Hormones; klíšťata; nádory prsu; Epigenesis, Genetic; Humans; zvířata; hormony; stárnutí; Female